Scrambling in Korean Meets the Labeling Theory - Myung-Kwan Park; 유용석 (Language & Information Society, 2019)
This paper investigates the nature of scrambling in Korean, which is a word order permuting operation in syntax. We re-characterize it in light of Chomsky’s(2013, 2005) recent theory of labeling. We are in keeping with the thesis that scrambling in Korean undergoes non-A, non-operator movement and adjoins to its target (Saito 1985 and thereafter). We show that because of the lack of obligatory agreement, there is no A vs. A’-distinction in this language, so that in overt syntax a scrambled expression enters into licensing relation just like an adjunct. Therefore, it cannot be deployed into the properly labeled structure in this level of syntactic component. To overcome the problem with labeling, it generally undergoes radical reconstruction to its underlying position, but it also markedly enters into semantic predication at the interface. KCI Citation Count: 1